Progressive transfusion and growth factor independence with adjuvant sertraline in low risk myelodysplastic syndrome treated with an erythropoiesis stimulating agent and granulocyte-colony stimulating factor. Issue 1 (2015) - Nautiyal, Kirtan; Li, Rui; Yellapragada, Sarvari; Thiagarajan, Perumal; Mims, Martha; Rivero, Gustavo
Abstract: Refractoriness to growth factor therapy is commonly associated with inferior outcome in patients with low-risk myelodysplastic syndrome (LR-MDS) who require treatment for cytopenias. However, the mechanisms leading to refractoriness are unknown. Here we describe a clinically depressed 74-year-old male with refractory cytopenia with multilineage dysplasia (RCMD) and documented growth factor refractory anemia after erythropoeisis stimulating agent (ESA) therapy, who attained transfusion and growth factor independence after the addition of sertraline to his medication regimen. Our case demonstrates hematological improvement-erythroid (HI-E) in growth factor refractory, low risk MDS and highlights a potential mechanistic link between common inflammatory diseases and LR-MDS. Highlights: Our case shows HI-E with sertraline in growth factor refractory, low risk MDS. We highlight a potential mechanism between common inflammatory diseases and LR-MDS. This is the first report of potential therapeutic role for SSRIs in myelodysplasia.